The History of Printing and Print Culture: Contexts and Controversies. (3rd May 2020) - Hinks, John
ABSTRACT: The history of printing and print culture is a dynamic and wide-ranging field of study, as the articles in this special issue demonstrate. By way of background, this introductory article briefly outlines the development of the field and highlights a number of controversial issues that have arisen within it. Although often considered part of 'the history of the book' (or 'book history'), much of the history of printing is concerned with the quotidian production of non-book material including a vast variety of ephemeral printed items known as 'jobbing printing'. Printed items, both books and ephemera, have made a significant contribution to the history of the Midlands. In particular, printing played a key role in the industrial development of the region and in the 'Midlands Enlightenment'.